GnRH-immunocastration: an alternative method for male animal surgical castration - Wang, Chun; Yang, Cuiting; Zeng, Yutian; Zhang, Ming (Frontiers in Veterinary Science, 2023)
Tranditional methods of mechanical and surgical castration have been employed over the years, but they fall short of meeting animal welfare requirements due to the associated risk of infection, pain, and stress. Immunocastration, specifically Gonadotropin-releasing hormone (GnRH)-immunocastration, targeting the hypothalamic-pituitary-testis (HPT) axis, has emerged as an animal-friendly alternative to surgical castration, effectively addressing these issues. This review seeks to systematically summarize the principles, development, current applications and challenges of GnRH-immunocastration, offering insights into its role in promoting animal welfare.